1988
DOI: 10.1063/1.100228
|View full text |Cite
|
Sign up to set email alerts
|

Schottky barrier height of InxAl1−xAs epitaxial and strained layers

Abstract: The Schottky barrier height of n-type semiconducting and semi-insulating InxAl1−xAs grown by molecular beam epitaxy has been determined on the lattice-matched composition, x=0.523, in tension and in compression relative to their (110) oriented InP substrates. For the semiconducting material in the composition range 0.43<x<0.62, the barrier height is φbn=0.62±0.05 eV while the anomalous rise and saturation of φbn at 1.2 eV of the semi-insulating material, within the same composition range, is attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Their data supplement results previously published by Lin et al 3 and Chu and co-workers. 4 They varied the compositional parameter x between 0.45 and 0.55. Figure 1 displays these data and also shows barrier heights reported by Best 5 for Au/AlAs and by Sadwick et al 6 and Gueissaz et al 7 for Al/Al 0.48 In 0.52 As contacts.…”
Section: Schottky Contacts On Ternary Compound Semiconductors: Composmentioning
confidence: 99%
“…Their data supplement results previously published by Lin et al 3 and Chu and co-workers. 4 They varied the compositional parameter x between 0.45 and 0.55. Figure 1 displays these data and also shows barrier heights reported by Best 5 for Au/AlAs and by Sadwick et al 6 and Gueissaz et al 7 for Al/Al 0.48 In 0.52 As contacts.…”
Section: Schottky Contacts On Ternary Compound Semiconductors: Composmentioning
confidence: 99%
“…When the cluster shape is approximated with a sphere, these binary clusters have been found to have diameters of less than 10 nm. Chu et al 2 concluded that AlAs clusters were present at certain growth conditions from observations of Schottky barrier heights at 1.2 eV in InAlAs. Using cross-sectional transmission electron microscopy ͑XTEM͒, McDevitt et al 3 found the average periodicity of the compositional fluctuations was on the order of 3-7 nm for a lattice matched ternary on indium phosphide ͑InP͒.…”
Section: Introductionmentioning
confidence: 98%
“…Compared with that of In Al As lattice-matched to InP, Schottky barrier height of strained Al-rich In Al As lattice-mismatched to InP has been verified to rise anomalously with the increase of fractional Al concentration and saturated at 1.2 eV [7], showing the possibility for this material used as Schottky contact material in E-HEMT's. In this paper, we demonstrate InAlAs/InGaAs E-PHEMT by introducing strained In Al As as barrier layer and titanium still as Schottky contact.…”
Section: Introductionmentioning
confidence: 98%